ON COMMON FIXED POINT THEOREMS FOR UNIFORMLY ASYMPTOTICALLY QUASI-NONEXPANSIVE MAPPINGS IN HYPERBOLIC SPACES - Nuntadilok, B.; Kingkam, P. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2025)
The aim of this manuscript is to establish a common fixed point theorem for two uniformly L-Lipschitzian and asymptotically quasi-nonexpansive non-self maps with respect to retraction P via implicit algorithm and to prove common fixed point results of two weakly inward and asymptotically quasi-nonexpansive mappings with respect to P satisfying condition (A) and condition (B), in a more general set up of hyperbolic space. Our results generalize, extend and improve some related results in the existing literature.